Functional Connectivity Analysis under Vigilance Decrement and Enhanced Mental States - Hassanin, Omnia (2020)
A Master of Science thesis in Biomedical Engineering by Omnia Hassanin entitled, “Functional Connectivity Analysis Under Vigilance Decrement and Enhanced Mental States”, submitted in June 2020. Thesis advisors are Dr. Hasan Al Nashash, Dr. Usman Tariq and Dr. Fares Yahya. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).